2023
DOI: 10.3389/fmats.2023.1165245
|View full text |Cite
|
Sign up to set email alerts
|

Processing, microstructure, properties, and applications of MoSi2-containing composites: a review

J. Tapia-López,
M. I. Pech-Canul,
H. M. García

Abstract: Intermetallic molybdenum disilicide (MoSi2) possesses unique physical, chemical, thermal, and mechanical properties that make it compatible with some ceramics (SiC, Al2O3) and metals (Cu, Al) to manufacture composite materials. Its current applications, chiefly limited to heating elements, can be expanded if its properties are judiciously combined with those of other materials like SiC or Al to produce ceramic- and metal-matrix composites with improved mechanical, thermal, functional, or even multifunctional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 142 publications
0
2
0
Order By: Relevance
“…The results indicated that as the thickness of the outer layer and close of porosity, the hardness values increased with adding of MoSi 2 , which significantly improved the micro hardness value Most likely, the hardness and wear resistance properties important factors such as coating structure and of coatings are more strongly affected by morphologies, and pores distribution than coatings thickness [30]. Furthermore, different sizes of pan-like or sphere-like geometric pores, which are the result of the molten liquid that swiftly hardened and left distinct borders around the pores, characterize the morphologies that may be observed in the structure.…”
Section: Coating Thickness and Hardnessmentioning
confidence: 95%
See 1 more Smart Citation
“…The results indicated that as the thickness of the outer layer and close of porosity, the hardness values increased with adding of MoSi 2 , which significantly improved the micro hardness value Most likely, the hardness and wear resistance properties important factors such as coating structure and of coatings are more strongly affected by morphologies, and pores distribution than coatings thickness [30]. Furthermore, different sizes of pan-like or sphere-like geometric pores, which are the result of the molten liquid that swiftly hardened and left distinct borders around the pores, characterize the morphologies that may be observed in the structure.…”
Section: Coating Thickness and Hardnessmentioning
confidence: 95%
“…Results from wear test carried out for different times (30,60,90,120 In general, the weight losses varied with duration of rubbing and normal load at constant sliding velocity, and there were some "negative weight losses" for coating C. The explanation for this case is that the surface of the sample contained asperities, and at the beginning of the test the frictional thrust increased, which resulted in increased debonding and sub-surface fracture of the asperities, and thereafter ,led to a clear loss of weight for ascertain duration of rubbing. After that, the surface was becoming smoother and the loss of weight remained almost non-existent, for Furthermore, the incorporation of MoSi 2 recorded the best improving in wear resistance among the other samples due to the high mechanical properties of MoSi 2 particles and their effects in filling the micropores [36], and therefore reducing the surface roughens.…”
Section: Dry Sliding Testsmentioning
confidence: 99%